Parameterized GSOR Method for a Class of Complex Symmetric Systems of Linear Equations (Journal of Mathematical Study, 2019)
A parameterized generalized successive overrelaxation (PGSOR) methodfor a class of block two-by-two linear system is established in this paper. The convergence theorem of the method is proved under suitable assumptions on iterationparameters. Besides, we obtain a functional equation between the parameters andthe eigenvalues of the iteration matrix for this method. Furthermore, an acceleratedvariant of the PGSOR (APGSOR) method is also presented in order to raise the convergence rate. Finally, numerical experiments are carried out to confirm the theoreticalanalysis as well as the feasibility and the efficiency of the PGSOR method and its variant.